Determinants of Firm Value: The Roles of Sustainability, Business Risk, and Dividend Policy with Profitability as a Mediating Variable - Khalisma, Mustofa Nur; Risman, Asep (Dinasti Publisher, 2025)
This study examines the impact of sustainability, business risk, and dividend policy on firm value, with profitability as a mediator. To provide empirical insights, the research utilizes data from a sample of 12 coal companies listed on the Indonesia Stock Exchange (IDX) over the period from 2019 to 2023. The research method employs panel data regression analysis to test the relationships among variables and the Sobel test to examine the mediating role. The results show that sustainability does not affect firm value, business risk has a positive effect on firm value, dividend policy does not affect firm value, and profitability has a positive effect on firm value. Then, sustainability has a positive effect on profitability, business risk does not affect profitability, and dividend policy has a negative effect on profitability. Furthermore, profitability is found to mediate the effect of sustainability and dividend policy on firm value, while profitability does not mediate the effect of business risk on firm value.